Analisis Pengaruh Pertumbuhan Ekonomi Dan Inflasi Terhadap Kemiskinan Di Sumatera Utara - Royan Abel Nadeak; Taufik Hidayat; Billy Sugianta Surbakti (Jurnal Manajemen Akuntansi (JUMSI), 2023)
Poor people are residents who have an average monthly per capita expenditure below the poverty line. The problem of poverty is a complex and multidimensional problem covering various aspects of human life, including the local government in North Sumatra. Efforts to eradicate poverty must pay attention to the root causes of poverty itself. The indicators used in this study are the rate of economic growth, inflation, and the amount of poverty. This study aims to analyze how much influence the rate of economic growth and inflation has had on the poor population in North Sumatra in the 2001-2020 period, both simultaneously and partially. The type of data used in this study is secondary time series data from 2001 to 2020. The data used is data obtained from the official website of the Central Statistics Agency (BPS) of North Sumatra. The analytical method used in this research is multiple linear regression analysis with Eviews statistical software. The results showed that the economic growth rate variable had a positive and insignificant effect on poverty in North Sumatra Province. Partially the inflation variable has a positive and significant effect on poverty in North Sumatra Province.